EXTRACT OF PROPOLIS IN CONTROL OF Penicillium sp. AND IN THE QUALITY OF CAULIFLOWER SEEDS - de Souza, E. P.; Perino, F. H. B.; Moscato, B. S.; Freitas, P. G. N.; Blumer, S.; Cardoso, A. I. I.; Bonini, C. S. B.; Bonini Neto, A. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Supplying the world demand for better quality foods and free of agrochemicals, alternative means have been studied for the control of fungi. Fungi of the genus Penicillium sp are known as storage fungi that degrade the seed reserve and decrease its viability. Given this fact, the objective of this study was to evaluate the effect of solutions of propolis extract on the control of the fungus Penicillium sp. in vitro and in the physiological quality of cauliflower seeds after treatment. The treatments consisted of concentrations of 0, 5, 10 and 20% of propolis extract. The study was divided into two stages. In the first one, the effect of propolis extract solutions on the development of the fungus in vitro was verified, and on the second the physiological quality of the treated cauliflower seeds. The experimental design was completely randomized for the two stages, with seven and six replications, respectively. The evaluated characteristics were: mycelial growth, and physiologic quality of seeds on germination, first germination count, shoot length and root of cauliflower seedlings. Concentration of 20% of the solution of propolis extract prevents the development of the fungus Penicillium sp. in vitro and does not affect the physiological quality of cauliflower seeds.